Recovery of Phenolic Compounds from Jackfruit Seeds Using Subcritical Water Extraction - Ravshanbek Sultanbekovich Alibekov; Siti Mazlina Mustapa Kamal; Farah Saleena Taip; Alifdalino Sulaiman; Abdugani Mutalovich Azimov; Klara Abdyrazahovna Urazbayeva (Foods, 2023)
Jackfruit is one of the major fruits cultivated in many Asian countries. Jackfruit seeds are generally disposed of into the environment, which causes an environmental concern that leads to biowaste accumulation. The seeds have excellent nutritional value, such as carbohydrates, protein, fats, minerals, and bioactive compounds. Bioactive compounds, such as phenolic, can be recovered from jackfruit seeds that could add value to the food and pharmaceutical industry. Thus, this study focused on utilizing subcritical water to extract the phenolic compounds from jackfruit seeds and correlate them with antioxidant activity (AA). The extraction of phenolic compounds was studied at different temperatures and extraction times. The highest total phenolic compounds (TPC) and AA were obtained by treating the jackfruit seed powder at 210 °C, 30 min, and 15% solid loading under subcritical water extraction (SWE) with 1.84 mg GAE/100 g (TPC) and 86% (AA). High correlation between the extracted TPC and AA of the jackfruit seed extracts was obtained (R2 = 0.96), indicating a significant positive relationship between TPC and AA. A higher amount of TPC was obtained via SWE as compared to Soxhlet extraction (1 h:0.53 mg GAE/100 g and 4 h:1.20 mg GAE/100 g). More pores were detected on the surface of the sample treated by SWE than using Soxhlet extraction. Thus, jackfruit seed extracts can be potentially beneficial in the fortification of fermented dairy or meat products.